Child Abuse: The Human Figure Drawing Test in Evaluating Minors - Lisi, Andrea; Valentina, Stallone; Giovanna, Tomasino Maria; Valeria, Affatati; Grattagliano, Ignazio (International Journal of Criminology and Sociology, 2013)
The Human Figure Drawing Test (HFDT) is widely used in clinical and forensic settings. The inappropriate use of this instrument is widespread. This article highlights the expressive and communicative value of children’s drawings in child abuse investigations. The drawings of 3 groups of children (11 certified as abused; 11 suspected of being abused, and 11 certified as non-abused) were examined in order to determine the appropriateness of their use in suspected cases of child abuse. The results of our study appear to be divergent. As of the writing of this article, there is no methodologically correct way in which to utilize this instrument that would reveal specific “graphic indicators of abuse” using the drawings of abused, or presumably abused children.